Model Pengembangan Kurikulum Pendidikan Nilai di Madrasah Tsanawiyah Negeri - Gunawan, Agus (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
Education value and national education both have same functions and goals in shaping a good personality towards students, therefore value education is very important to build the character of the Indonesia people. The aim of this study is to determine the governance model of curriculum development of the value education and development barriers of curriculum of the value education in character building efforts. This research uses descriptive quantitative method, and sampling is taken by census, that is 46 teachers. Data were analyzed using Likert scale and also analyzed descriptively. The results show two conclusions. First, the overall assessment of the scores on the model of curriculum development of the value education in Madrasah Tsanawiyah Negeri 1 Serang City included in both categories in accordance with the average score of 4.00 and the achievement of maximum score 82. Second, the model of curriculum development of the value education in Madrasah Tsanawiyah Negeri 1 Serang City is not yet optimal, because there are still some obstacles in developing the curriculum of the value education in Madrasah Tsanawiyah Negeri 1 Serang City.